Implications of Indonesian Migrant Worker Fluctuations on Taiwan Trade Rate Under the New Southbound Policy Framework (2019-2023) - Rahma Sintya Devi; Septyanto Galan Prakoso; Ihya Pradnya Sayoga; Hasna Dherin Syakira (Andalas Institute of International Studies UNAND, 2025)
The influence of China has weakened Taiwan's position in global diplomacy. China emphasizes that countries that establish diplomatic relations with Taiwan will lose relations with China. In response, Taiwan introduced the New Southbound Policy (NSP) as a hedging strategy to counteract diplomatic isolation through cooperation. This policy seeks to strengthen economic, cultural, and technological relations with countries in South and Southeast Asia, including Indonesia. Taiwan and Indonesia have enhanced trade relations through programs promoting people-to-people connectivity involving individuals and civil society networks. A key aspect of this cooperation is the employment of Indonesian migrant workers in Taiwan, which relates to the New Economics of Labor Migration. NELM is a theory that puts emphasis on the impact of migrant labor and remittances on the trade balance of a country. This paper will analyze the effect of the existence of Indonesian Migrant Workers on remittances and the trade balance of Taiwan in the ensuing NSP. Quantitative approach used by utilizing simple linear regression to sharpen the result based on the data that were identified using the official government websites, datasets, journal articles, and others. Results indicate that there are impacts caused by the existence of Indonesian workers on Taiwan’s trade balance by 55.5% and remittances 32.7%, respectively. Although other reasons, including Indonesian visitors, also contribute to the process. NSP was launched to balance geopolitical tensions and link trade, technology, education, labor, and cultural exchange.